Association between intensity modulated radiotherapy and survival in patients with stage III non-small cell lung cancer treated with chemoradiotherapy. (June 2017) - Koshy, Matthew; Malik, Renuka; Spiotto, Michael; Mahmood, Usama; Rusthoven, Chad G.; Sher, David J.
Highlights: Intensity modulated radiation therapy (IMRT) is associated with a small survival benefit in patients with stage III non-small cell lung cancer. IMRT use in lung cancer was associated with a decrease in radiation treatment interruptions. This radiation technique should be strongly considered in the management of this malignancy. Abstract: Purpose: To determine the effect of radiotherapy (RT) technique on treatment compliance and overall survival (OS) in patients with stage III non-small lung cancer (NSCLC) treated with definitive chemoradiotherapy (CRT). Methods and Materials: This study included patients with stage III NSCLC in the National Cancer Database treated between 2003 and 2011 with definitive CRT to 60–63 Gray (Gy). Radiation treatment interruption (RTI) was defined as a break of ≥4 days. Treatment technique was dichotomized as intensity modulated (IMRT) or non-IMRT techniques. Results: Out of the cohort of 7492, 35% had a RTI and 10% received IMRT. With a median follow-up of surviving patients of 32 months, the median survival for those with non-IMRT vs. IMRT was 18.2 months vs. 20 months ( p < 0.0001). Median survival for those with and without an RTI ≥ 4 days was 16.1 months vs. 19.8 months ( p < 0.0001). Use of IMRT predicted for a decreased likelihood of RTI (odds ratio, 0.84, p = 0.04). On multivariable analysis for OS, IMRT had a HR of 0.89 (95% CI: 0.80–0.98, p = 0.01) and RTI had a HR of 1.2 (95% confidence interval (CI): 1.14–1.27, p = 0.001). Conclusions: IMRT was associated with small but significant survival advantage for patients with stage III NSCLC treated with CRT. A RTI led to inferior survival, and both IMRT and RTI were independently associated with OS. Additional research should investigate whether improved tolerability, reduced normal tissue exposure, or superior coverage drives the association between IMRT and improved survival.